PENGARUH BUDAYA ORGANISASI, KOMITMEN ORGANISASI DAN PENERAPAN PRINSIP-PRINSIP GOOD CORPORATE GOVERNANCE (GCG) TERHADAP KINERJA PERGURUAN TINGGI DENGAN PENDEKATAN BALANCED SCORECARD (BSC) - Fenty Astrina (Jurnal Ilmiah Ekonomi Global Masa Kini)
The purpose of this research are to study and analyze the  influence of organizational culture, organizational commitment and implementation good corporate governance principles towards university performance in Muhammadiyah University both simultaneously and partially. This research conducted at 7 faculties in Muhammadiyah University  with amount of respondents are 223, from that amount there ara 82 declared complete for analysis. The data collecting was carried out by spreading questionnaires to lecturer and employee . The  technical method of simple purpossive sampling. The tool of analyze is path analysis. The result on this research and hypothesis testing show that: (1) there is correlation among organizational culture  and organizational commitment but not significant; (2) simultaneously, organizational culture, organizational commitment and good corporate governance had significant influence to university performance; (3) partially, organizational culture and organizational commitment had positive influence but not significant to university performance,  good corporate governance had positive influence and significant to university performance.Managerial imlpication of the study is to focus more on increasing lecturer an employee commitment and socialize organization culture among lecturers and employees for increasing university performance.Keyword : Organization Culture, Organization Commitment, Good Corporate Governance, Organizational  Performance.